Changes in Microbiota Composition Along the Metamorphosis Developmental Stages of Chironomus transvaalensis - Sela, Rotem; Laviad-Shitrit, Sivan; Halpern, Malka (Frontiers in Microbiology, 2020)
Chironomids (Diptera; Chironomidae), also known as non-biting midges, are one of the most abundant insects in freshwater habitats. Our aim was to understand whether the metamorphosis developmental stages affects the endogenous microbiota composition of Chironomus transvaalensis. Towards our objective, we analyzed the endogenous microbiota composition of C. transvaalensis’ four life stages: egg masses, larvae, pupae and adults. Significant differences were found between the microbiota composition of the different developmental stages of this Chironomus species. We observed a decline in bacterial diversity as the insect evolved from egg mass to adult, while the highest richness was observed in the pupal stage. Although there were significant differences between the microbiota composition of each life stage, a bacterial core which included 27 Amplicon Sequence Variants (ASVs) was found in all the developmental life stages (in ≥75% of samples). Chironomids are natural reservoirs of Vibrio cholerae and Aeromonas species and the Vibrio and Aeromonas ASVs were part of the core bacteria. The presence of the ompW gene, which is specific to V. cholerae, confirmed the presence of this species in all the chironomid's life stages. Thus, the results provide important insights about the host–microbe interactions in chironomids with a specific understanding of chironomids-Vibrio-Aeromonas-microbiota interactions.